Footstep sounds synthesis: Design, implementation, and evaluation of foot–floor interactions, surface materials, shoe types, and walkers' features. (June 2016) - Turchet, Luca
Abstract: This paper presents a novel footstep sound synthesizer based on physical and physically inspired models coupled with additive synthesis and signals multiplication. Several types of foot–floor interactions are simulated (e.g., different types of steps in walking and running or the sliding of the foot on the floor). Moreover, different types of shoes and ground materials (solid, aggregate, liquid, and hybrids) are synthesized, along with the modeling of some anthropomorphic features of the walkers (i.e., body size and foot-length). The design choices underlying the proposed synthesis methods were made according to four main points: (i) auditory perceptual relevance, i.e., ecological validity; (ii) cartoonification approach; (iii) parametric temporal control; (iv) real-time utilization. Moreover, four types of control for the involved synthesis algorithms are discussed. Firstly, a control strategy is proposed in order to generate sequences of footstep sounds. Secondly, the design choices underlying the tuning of the synthesis parameters are illustrated. Thirdly, a control strategy is presented to provide footstep sounds designers and foley artists with a tool to create perceptually compelling sounds in an intuitive manner. Fourthly, control techniques are discussed for the interactive case in presence of different types of locomotion interfaces along with their differences with the non-interactive control when locomotion is passively simulated. Finally, four perceptual experiments successfully assessed the validity of the proposed techniques.